Corporate behavioural finance – the case of Lithuania - Jurevičienė, Daiva; Bikas, Egidijus; Keliuotytė-Staniulėnienė, Greta; Novickytė, Lina; Dubinskas, Petras (Business, Management and Economics Engineering, 2013)
Behavioural finances became especially important in recent years. Majority of studies covers individual investor decision making factors while corporate customers’ investment behaviour, as a rule, encompass liability side (capital expenses, financing and structure; dividend policy; assessment of potential investment projects, etc.). This paper aims to establish investment possibilities of nonfinancial corporate investors in financial markets, basing on accomplished survey of companies managers, and strives to determine enterprise investment in financial assets assumptions. Though the results of the survey sample not fully meets the requirements of representativeness but satisfy the minimum margin error – up to 10 percent – acceptable level.